The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1126/science.1188235
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation via Symbiosis: Recent Spread of a Drosophila Defensive Symbiont

Abstract: Recent studies have shown that some plants and animals harbor microbial symbionts that protect them against natural enemies. Here we demonstrate that a maternally transmitted bacterium, Spiroplasma, protects Drosophila neotestacea against the sterilizing effects of a parasitic nematode, both in the laboratory and the field. This nematode parasitizes D. neotestacea at high frequencies in natural populations, and, until recently, almost all infections resulted in complete sterility. Several lines of evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
538
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(553 citation statements)
references
References 36 publications
10
538
1
4
Order By: Relevance
“…While documented fitness benefits of symbionts have been primarily nutritional, a number of recent studies have reported protective effects of symbiont infection, suggesting that defense against natural enemies may be another major route facilitating invasion of heritable symbionts into host populations [5-7]. Insect symbionts of diverse bacterial lineages have been shown to provide substantial protection against fungal pathogens [8,9], viruses [10,11], predators [12,13], parasitoids [14-17] and parasitic nematodes [18]. Despite increasing awareness of the roles of these bacteria in protecting hosts, little is known about natural enemy responses to this line of defense.…”
Section: Introductionmentioning
confidence: 99%
“…While documented fitness benefits of symbionts have been primarily nutritional, a number of recent studies have reported protective effects of symbiont infection, suggesting that defense against natural enemies may be another major route facilitating invasion of heritable symbionts into host populations [5-7]. Insect symbionts of diverse bacterial lineages have been shown to provide substantial protection against fungal pathogens [8,9], viruses [10,11], predators [12,13], parasitoids [14-17] and parasitic nematodes [18]. Despite increasing awareness of the roles of these bacteria in protecting hosts, little is known about natural enemy responses to this line of defense.…”
Section: Introductionmentioning
confidence: 99%
“…Although our results do not allow us to distinguish between these, observation of similar effects of two Spiroplasma strains (MSRO and hy1; poulsonii clade), in two distantly related Drosophila hosts (D. hydei and D. melanogaster) against two congeneric but distantly related parasitoid wasps (Lh and Lb), suggests that the mechanism might be quite general. Furthermore, the mycophagous fly D. neotestacea harbors a non-male-killing Spiroplasma strain (also within the poulsonii clade) that inhibits growth of Howardula aoronymphium, a parasitic nematode of adult hemocoel (Jaenike et al, 2010b). Thus, assuming the same mechanism is responsible for growth inhibition of the two types of endo-macroparasites (i.e., wasps and nematodes), this trait may have been present in the ancestor of the poulsonii clade, which includes male-killing and non-male-killing strains associated with several other species of Drosophila (e.g., D. nebulosa, D. willistoni and D. simulans; Haselkorn et al, 2009).…”
Section: Wasp-killing Mechanismmentioning
confidence: 99%
“…Several bacterial symbionts of aphids confer protection against parasitoid wasps (Oliver et al, 2003(Oliver et al, , 2005Vorburger et al, 2009) and fungi (Scarborough et al, 2005;Lukasik et al, 2012). Spiroplasma bacteria confer protection against fungi in the pea aphid (Lukasik et al, 2012), against a nematode in Drosophila neotestacea (Jaenike et al, 2010b) and against a parasitoid wasp in Drosophila hydei . Wolbachia has been shown to increase resistance or tolerance of Drosophila and mosquitoes against RNA viruses and against the protozoan parasite Plasmodium (Hedges et al, 2008;Teixeira et al, 2008;Moreira et al, 2009;Osborne et al, 2009;Bian et al, 2010;Frentiu et al, 2010;Zele et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In insects, bacterial symbionts can improve host fitness, and recent studies have shown that these symbionts respond to the selection on their host's phenotype by increasing in frequency, hence permitting the adaptation of the host [4][5][6][7][8] . For example, within a few years, a strain of a maternally transmitted bacterium belonging to the Spiroplasma genus has invaded many North American populations of its host, Drosophila neotestacea, because of the protection it provides against a parasitic nematode 6 .…”
mentioning
confidence: 99%
“…Again, such conflicts are well-described in insect-bacterium associations. Indeed, several bacteria that have recently been shown to be involved in host adaptation were previously known as parasitic manipulators of sex determinism and reproduction (for example, REFS 5,6). Conflicts may even occur when components of inclusive inheritance are transmitted in the same manner.…”
mentioning
confidence: 99%